(untitled) (Research, Society and Development, 2021)
Objective: To report an experience lived by the authors of the study in a waiting room of an Ambulatory in Belém do Pará, regarding the relationship of citizens’ perception of Sexually Transmitted Infections. Method: Explains an experience report, carried out by Nursing and Medical students at the Specialty Clinic for users who were expecting care. The construction of the activity was based on the stages of the Arco de Maguerez: I- It was the elaboration of the activity in the Outpatient Clinic; II- Identification of key points, possible vulnerabilities, and target audience; III- Theorization, research through bibliographic studies; IV- Search for technological innovations related to the problem, and construction of the material, highlighting the main STIs; V- Carrying out the educational action. Results and Discussion: The educational activity provided important dialogues about STI knowledge. Fragility was perceived in terms of knowledge and, therefore, greater interest in the transmission of STIs. Final Considerations: It is concluded that it is fundamental to develop strategies aimed at public health, with a focus on prevention, such as the inclusion of actions aimed at qualifying knowledge about STIs, using tactics that directly or indirectly reach a wide audience, especially the population with low education and low socioeconomic status.